RESPON JAGUNG MANIS (Zea mays sacaratha sturt. L) TERHADAP PEMBERIANBOKASHI TANDAN KOSONG KELAPA SAWIT PADA INCEPTISOL DESA BOBO - pole, Isnawati A.; Wahyudi, Imam; Ete, Andi (AGROTEKBIS, 2018)
The purpose of this research is to study the response of sweet corn plants on the application of unfilled Palm Oil bunches Bokashi on Inceptisol. The study was conducted in February until September 2015 at the Faculty of Agriculture, University Tadulako. The study used Randomized Block Design (RBD) with the application of unfilled Palm Oil Bunches (EFB) Bokashi treatment at a dose of A = 0 t ha-1 (control) B = 5 t ha-1 (14.3 g / pot) C = 10 t ha-1 (28.6 g / pot) D = 15 t ha-1 (42.9 g / pot) E = 20 t ha-1 (57.1 g / pot) F = 25 t ha1 (71.4 g / pot) and G = 30 t ha-1 (85.7 g / pot). The result of the research showed that the application of the bokashi at a dose of 20 ton h-1 is able to provide optimal results in the growth of plant height, leaf area, stem diameter and number of leaves and the production of sweet corn. Keywords: Bokashi Oil Palm Empty Fruit Bunch (EFB), Bokashi Different Dose, Plant sweet corn (Zea mays L sacaratha strut),